Madrasah Aliyah Students' Interest in the Islamic Counseling Study Program of the Faculty of Ushuluddin, Adab and Dakwah IAIN Curup - Verolyna, Dita; Yusro, Ngadri (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This study aims to observe how the interest of Madrasah Aliyah students in Rejang Lebong Regency to continue their studies at the BPI IAIN Curup Study Program. This research uses quantitative methods and descriptive approaches. The population in this study were all madrasah aliyah students who were in class XII, and the sample used a volunteer or voluntary technique where anyone who was willing to fill out a questionnaire would be the sample. The total population was 324 students and 196 people filled out the questionnaire. The results of the questionnaire are displayed in a simple frequency table. Based on the results of the study, it was found that the interest score of madrasah aliyah students to continue their studies to the BPI IAIN Curup Study Program was 49.49%. This is reinforced by the average score of 54, median of 53 and mode of 50. Motivation indicators get a moderate score (44%), perception gets a moderate score (41%), family gets a moderate score (56%), facilities get a low score ( 33%) and socialization got a moderate score (57%). Thus, the overall interest of madrasah aliyah students in continuing their studies to the BPI study program is moderate